Pilot scale conversion of wheat straw to ethanol via simultaneous saccharification and fermentation. (January 2015) - Saha, Badal C.; Nichols, Nancy N.; Qureshi, Nasib; Kennedy, Gregory J.; Iten, Loren B.; Cotta, Michael A.
Highlights: Conversion of wheat straw to ethanol was scaled up at pilot scale. Dilute acid pretreated wheat straw was bioabated by growing a fungus aerobically. Recombinant bacterium fermented all sugars to ethanol. Maximum ethanol produced from 124 g wheat straw was 36 g in 83 h. Ethanol yield was 0.29 g/g wheat straw which is 86% of theoretical ethanol yield. Abstract: The production of ethanol from wheat straw (WS) by dilute acid pretreatment, bioabatement of fermentation inhibitors by a fungal strain, and simultaneous saccharification and fermentation (SSF) of the bio-abated WS to ethanol using an ethanologenic recombinant bacterium was studied at a pilot scale without sterilization. WS (124.2 g/L) was pretreated with dilute H2 SO4 in two parallel tube reactors at 160 °C. The inhibitors were bio-abated by growing the fungus aerobically. The maximum ethanol produced by SSF of the bio-abated WS by the recombinant Escherichia coli FBR5 at pH 6.0 and 35 °C was 36.0 g/L in 83 h with a productivity of 0.43 g L −1 h −1 . This value corresponds to an ethanol yield of 0.29 g/g of WS which is 86% of the theoretical ethanol yield from WS. This is the first report on the production of ethanol by the recombinant bacterium from a lignocellulosic biomass at a pilot scale.